1998
DOI: 10.1038/eye.1998.54
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of axial length in the calculation of intraocular lens power

Abstract: Purpose Accurate measurement of ocular axial length is essential for accurate intraocular lens Conclusion The use of a single high-quality axia.1length measurement was as accurate as the mean of three acceptable axial length measurements in the calculation of IOL power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…The coefficient of repeatability for intra- and intersession repeatability using the LenStar are impressive (⩽2% of the average value for each biometric measure) and at least comparable with the IOLMaster10 21 and ultrasound 2 3. As expected, using the average of repeated measurements decreases the variability, and this can be further improved by excluding the most divergent of the results as allowed by the functionality of the LenStar software.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The coefficient of repeatability for intra- and intersession repeatability using the LenStar are impressive (⩽2% of the average value for each biometric measure) and at least comparable with the IOLMaster10 21 and ultrasound 2 3. As expected, using the average of repeated measurements decreases the variability, and this can be further improved by excluding the most divergent of the results as allowed by the functionality of the LenStar software.…”
Section: Discussionsupporting
confidence: 56%
“…However, the clinical significance of these effects are minor with the 0.01 mm difference in axial length equating to <0.03 D 6. The greater variability when the device was compared with applanation ultrasonography will be in part due to the lower resolution of this technique2 3 and because laser light is reflected from the retinal pigment epithelium, in contrast to ultrasound waves which are reflected from the internal limiting membrane 18. A compensation to more closely reflect ultrasound values can be selected in the LenStar software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have recommended an average of three serial measurements of AL be taken 11 . However, it has also been suggested that a single high‐quality AL measurement is sufficiently accurate in the context of calculation of IOL power 12 . Several earlier studies established that contact methods produce shorter AL measurements than immersion methods, although repeatability was similar with both techniques 6,7,13 .…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the term EL will refer to the distance cornea-retina and distinctions will be made when referring to axial or peripheral EL. EL has been long considered for its role in many areas including cataract surgery for intraocular lens power calculations and other surgical procedures such as strabismus surgery, [2][3][4] ocular disease development and progression, ocular development, refractive errors, 5,6 and ocular shape. [7][8][9] In this regard, accuracy of the EL measurement is paramount with reports indicating an error of 0.10 mm results in refractive errors of 0.20-0.30 D magnitude (assuming normal eye dimensions).…”
mentioning
confidence: 99%